Evolutionary Multi-Agent Systems From Inspirations to Applications - Byrski, Aleksander; Kisiel-Dorohinicki, Marek; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book addresses agent-based computing, concentrating in particular on evolutionary multi-agent systems (EMAS), which have been developed since 1996 at the AGH University of Science and Technology in Cracow, Poland. It provides the relevant background information on and a detailed description of this computing paradigm, along with key experimental results. Readers will benefit from the insightful discussion, which primarily concerns the efficient implementation of computing frameworks for developing EMAS and similar computing systems, as well as a detailed formal model. Theoretical deliberations demonstrating that computing with EMAS always helps to find the optimal solution are alsoincluded, rounding out the coverage.
Preface -- Part I Concept and formal model: Contemporary methods of computational intelligence -- Agent-based computing -- Formal aspects of agent-based metaheuristics -- Part II Design and implementation: Agent-based and component inspirations -- Implementation aspects of agent-based computing systems -- AgE Computing Environment -- Part III Experimental results: EMAS in optimization problems -- Tuning of EMAS parameters -- Final remarks -- References.
Keywords: Computational intelligence; Artificial intelligence; Algorithms; Computational Intelligence; Artificial Intelligence; Algorithms